The influence of PjBL based on 21CLD self-regulation dimension using google sites to creativity and self-regulation - Ahadiah, Rima; Juhanda, Aa; Hendrawati, Hendrawati; Nuranti, Gina (Universitas Wiralodra, 2024)
This study was motivated by the low self-regulation of students and the lack of creativity training in the form of ICT in biology learning. This study aims to determine the effect of PjBL based on 21CLD self-regulation dimension using Google Sites on creativity and self-regulation of high school students on excretory system material. The research method used was Quasi Experiment with Post Test Only Non-Equivalent Control Group Design. The research samples were XI D class as the experimental class and XI I as the control class. The instruments used are product assessment sheets, questionnaires, and observation sheets. The research results showed that student creativity in the experimental class on excretory system material obtained an average value of 84.8 and self-regulation of 86.6, with an excellent category. The results of the hypothesis test obtained a significance value of 0.001 on creativity data and 0.002 on self-regulation data (p <0.05). The result of the correlation test obtained a significance value of 0.001 <0.05 with a Pearson Correlation value of 0.539, which indicates the level of relationship is included in the medium category. From this study, it was concluded that PjBL based on 21CLD self-regulation dimension using Google Sites, had an effect on creativity and self-regulation of high school students in the excretory system material. The finding in this study is that the PjBL model based on 21CLD self-regulation dimension is much better for practicing self-regulation compared to creativity.